THE CURRENT SITUATION OF CONSTIPATION AND SOME RELATED FACTORS AMONG STUDENTS OF THAI NGUYEN UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of constipation in students of Thai Nguyen University of Medicine and Pharmacy; Analyze some factors related to constipation in this group of students.Methods: Cross-sectional descriptive study on 776 students from year 1 to year 6, conducted from January to November 2025. Constipation was determined according to the ROME IV criteria, and stool characteristics were assessed using the Bristol scale. Demographic, dietary, lifestyle, and psychological information were collected using a standardized questionnaire. Data was analyzed using SPSS 22.0.Results: The constipation rate among students was 7.0%. Many related factors were statistically significant, including: family history of constipation (64.8%), low fiber intake (77.8%), low physical activity (68.5%), sleep ≤ 6 hours/day (55.6%), and stress (81.5%) (p < 0.05). Demographic characteristics, such as age group (21–25), field of study, and living in a dormitory, also significantly affected the risk of constipation. No significant difference was noted between men and women.Conclusion: The rate of constipation in students is not high but is clearly influenced by lifestyle factors, especially diet, exercise, sleep, and stress.
Keywords: Constipation, student, Thai Nguyen University of Medicine and Pharmacy